Best Practices for Database Security in the Age of AI - Sandeep Kumar Nangunori (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Database security has seen a dramatic change as a result of artificial intelligence’s incorporation into contemporary technology, bringing with it previously unheard-of opportunities as well as obstacles. This thorough article looks at how businesses can use AI capabilities to safeguard sensitive data assets while fortifying their database security postures. With an emphasis on financial institutions and healthcare organizations, it looks at the changing threat landscape, crucial security measures, and practical implementation tactics across a range of sectors. The article further demonstrates the efficacy of threat detection systems, sophisticated encryption techniques, AI-powered security solutions, and thorough audit frameworks. It illustrates the vital significance of putting in place multi-layered security techniques that combine conventional safeguards with AI-enhanced protective measures through in-depth case studies and empirical analysis.